2012
DOI: 10.1037/a0027411
|View full text |Cite
|
Sign up to set email alerts
|

Holistic person processing: Faces with bodies tell the whole story.

Abstract: Faces and bodies are typically encountered simultaneously, yet little research has explored the visual processing of the full person. Specifically, it is unknown whether the face and body are perceived as distinct components or as an integrated, gestalt-like unit. To examine this question, we investigated whether emotional face-body composites are processed in a holistic-like manner by using a variant of the composite face task, a measure of holistic processing. Participants judged facial expressions combined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
104
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 146 publications
(112 citation statements)
references
References 93 publications
5
104
3
Order By: Relevance
“…The same facial expression can vary in appearance when presented with different bodily expressions; for example, a facial expression may be classified as angry when presented in the context of a body expressing anger, but disgusted when presented in the context of a body expressing disgust (Aviezer et al, 2008;Aviezer, Trope, & Todorov, 2012b). These findings imply that the attribution of affective states involves the integration of emotion cues from across the face and body.…”
Section: Introductionmentioning
confidence: 79%
“…The same facial expression can vary in appearance when presented with different bodily expressions; for example, a facial expression may be classified as angry when presented in the context of a body expressing anger, but disgusted when presented in the context of a body expressing disgust (Aviezer et al, 2008;Aviezer, Trope, & Todorov, 2012b). These findings imply that the attribution of affective states involves the integration of emotion cues from across the face and body.…”
Section: Introductionmentioning
confidence: 79%
“…Additionally, it was found that emotion recognition from face-body composites is based on holistic processing (Aviezer, Trope, & Todorov, 2012). To our knowledge, only Abbas and Duchaine (2008) examined the role of holistic processing in judgments of facial attractiveness.…”
Section: Introductionmentioning
confidence: 99%
“…Recently some studies attempted to investigate the influence of context on facial expression processing. These studies demonstrated that visual scenes (Lee et al, 2012;Righart and de Gelder, 2006, 2008a, 2008b, body expressions (Aviezer et al, 2008(Aviezer et al, , 2011(Aviezer et al, , 2012a(Aviezer et al, , 2012bMeeren et al, 2005), emotional words and verbal description (Carroll and Russell, 1996;Kim et al, 2004;Schwarz et al, 2013), emotional voices ( and Müller et al, 2011;Pourtois et al, 2000) affect emotional recognition from facial expressions. Scenes which faces are embedded in provided typical visual context.…”
Section: Introductionmentioning
confidence: 94%